2006
DOI: 10.1097/01.blo.0000200236.84189.87
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Osteogenic Response of Rat Bone Marrow Cells to bFGF and BMP-2 Treatments

Abstract: Basic fibroblast growth factor (bFGF) and bone morphogenetic protein-2 (BMP-2) are actively pursued for stimulation of bone formation. To assess their promise for systemic therapy of osteoporosis, we ascertained the effects of bFGF and BMP-2 on bone marrow cells in vitro. Bone marrow cells were obtained from young (8 weeks) and adult (32 weeks) rats by femoral aspiration and were exposed to osteogenic medium (ie, basal medium with 10 mM beta-glycerolphosphate and 100 nM dexamethasone) containing the growth fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 35 publications
3
42
0
Order By: Relevance
“…The addition of bFGF to dentin pulp cultures suppressed the increases in ALPase activity, SPARC synthesis, and their mRNA levels [45]. However, other studies have shown that bFGF is associated with osteogenic properties especially when used in combination with bone forming proteins such as BMPs [46,47]. Our present studies, however, are the first to show suppression of elastin calcification by bFGF at 28 days in subdermal implantation model; however, whether this holds true for long-term studies and in the circulatory environment is unknown and needs further study in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of bFGF to dentin pulp cultures suppressed the increases in ALPase activity, SPARC synthesis, and their mRNA levels [45]. However, other studies have shown that bFGF is associated with osteogenic properties especially when used in combination with bone forming proteins such as BMPs [46,47]. Our present studies, however, are the first to show suppression of elastin calcification by bFGF at 28 days in subdermal implantation model; however, whether this holds true for long-term studies and in the circulatory environment is unknown and needs further study in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Since recombinant human BMP-2 (rhBMP-2) became available, many animal studies have been performed examining the induction of bone formation following implantation of rhBMP-2 using various carriers. 34,36,38,46,48 Fibroblast growth factor (FGF) was originally identified from extracts of the pituitary gland and brain, and has been demonstrated to stimulate the proliferation of fibroblasts. 22 The activity was mainly attributed to two similar proteins, acidic and basic fibroblast growth factor (bFGF, also known as bFGF-2).…”
Section: Introductionmentioning
confidence: 99%
“…[71][72][73] An inhibitory effect on the production of differentiation markers like alkaline phosphatase activity and induction of mineralization were also seen in cultures containing FGF-2/-9 in combination with BMP-2 in a 1:5 ratio or with osteogenic medium. 71,73,74 However, in cultures containing FGF-2 and BMP-2 at a ratio of 1:10 or higher, the combination had a stimulatory effect on the bone differentiation markers compared to BMP alone. 70 These studies suggest a ratio-dependent FGF/BMP effect in which the mitogenic FGF stimulus overrules the BMP-induced osteogenic differentiation at high FGF concentrations.…”
mentioning
confidence: 99%